Antifungal and Antioxidant Activity of Thiourea Derivatives Against Nosocomial Candida auris Strains Isolated in Romania - Marina Ionela Nedea (Ilie); Carmellina Daniela Bădiceanu; Irina Gheorghe-Barbu; Ioana Cristina Marinaș; Radu Pericleanu; Rareș-Ionuț Dragomir; Andreea Ștefania Dumbravă; Ana Maria Dascălu; Dragoș Șerban; Corneliu Tudor; Madălina Solomon (Preda); Oana Popescu; et al. (Molecules)
Nosocomial fungal infections caused by Candida auris pose a threat to public health due to their increased resistance to common antifungal drugs. Four thiourea derivatives of 2-thiophenecarboxylic acid were evaluated for their antifungal and antioxidant activity. The antifungal activity of the compounds was tested against strains of C. auris isolated from a hospital in Romania. With a notable inhibitory effect on C. auris biofilm growth and microbial adherence, the ortho-methylated derivative (SB2) showed the highest antifungal activity. Furthermore, emphasizing the impact of structural factors on the electron-donating capacity of these compounds, antioxidant activity assays (DPPH, FRAP, TEAC and CUPRAC) identified the SB2 compound as having the highest antihemolytic and antioxidant effects. The low cytotoxicity validated by hemocompatibility assays makes these compounds options for antifungal treatment. The results show that antifungal and antioxidant action is greatly influenced by structural modifications, especially the position of the methyl group on the aromatic ring. The possible clinical uses of these molecules as drugs for the treatment of multidrug-resistant C. auris infections needs further investigation.